The Role of Financial Literacy in Developing Financial Management Skills in Early Children - Susanti, Illa; Kemala, Ratu (Kompartemen: Kumpulan Orientasi Pasar Konsumen, 2023)
This research aims to describe the role of financial literacy in developing financial management skills in early childhood, using descriptive qualitative methods. This research was conducted in several elementary schools, where data was collected through observation, in-depth interviews with teachers and parents, as well as analysis of documents and school records related to the curriculum and financial learning activities. The results of this research show that financial literacy plays a crucial role in shaping children's understanding of money, saving and spending. Children who are exposed to basic financial concepts from an early age demonstrate a more mature understanding of the value of money and the importance of financial management. In addition, it was found that interactive and engaging financial literacy teaching can increase children's interest and understanding of this topic. This research also reveals that support from parents and teachers is very important in developing children's financial literacy. Collaboration between school and home is an important factor in ensuring children receive consistent and effective financial education. Based on these findings, this study recommends more intensive integration of financial literacy in primary school curricula and closer collaboration between schools and parents in educating children about financial management. In conclusion, financial literacy is an important aspect in early childhood education and has a significant impact on the formation of their financial management skills. The implications of this research are valuable for the development of educational policies and teaching practices in schools.